Solid state power controller - Ng, Tze Wei (Nanyang Technological University, 2021)
The advancement of technology in the field of electrical and electronics engineering has introduced a concept and developing pattern for All-Electric and More-Electric Aircraft (MEA/AEA) system and design. A MEA has significant advantages over a conventional mechanical system in its weight, cost, and space. This will essentially allow the replacement of the non-electrical systems on a conventional aircraft such as the hydraulic and pneumatic system with an electrical system. The changes to an electrical system from a mechanical system will result in a rise of voltage level in the aircraft. Hence, constant monitoring for the electrical fault signals will be required to prevent the aircraft from damage. Thus, there is a need to replace the conventional protection devices with a Solid-StatePower Controller (SSPC). SSPC can provide a constant flow of current during the normal conditions and have a faster reaction time. This report will demonstrate the design, testing,and development of the SSPC.